Sistem Pendukung Keputusan Penilaian Kinerja Aparatur Desa Berbasis Web Menggunakan Metode Profile Matching: (Studi Kasus: Desa Wee Limbu) - Yunike Wolla Gollu; Andreas Ariyanto Rangga; Paulus Mikku Ate (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
The problem raised is how to build a web-based decision support system for village apparatus performance assessment using the profile matching method, Kashus study at the Wee Limbu village office, southwest Sumba district. help carry out assessments using the profile matching method which is carried out to determine the apparatus' recommendations in the assessment system based on behavioral aspects, this decision making process is assisted by a decision support system. One of the methods used is Profile Matching, which is a method that compares the criteria for which alternative candidate places are selected. The road is suitable to be built according to the criteria determined by the Verification Body so that a difference value is obtained which is usually called the gap value. The decision support system designed is a web-based decision support system for assessing apparatus performance using the profile matching method